Pengembangan Sistem Informasi Manajemen Data Gapoktan Menggunakan Metode Fountain - Eva Argarini Pratama; Ahmad Nouvel; Sutrisno Sutrisno (TIN: Terapan Informatika Nusantara, 2026)
Data management in Farmers Group Associations (Gapoktan) is still largely done manually, causing various problems, such as data duplication, difficulty in finding information, delays in preparing reports, and a high risk of document loss. This condition also exists in Gapoktan in the Sokaraja area, Banyumas Regency, which requires an integrated system to support more effective and efficient organizational data management. This study aims to develop a web-based Gapoktan Data Management Information System using the Fountain method as a software development model. The study used a Research and Development (R&D) approach with the research location at Gapoktan in the Sokaraja area, Banyumas. Data collection was carried out through observation, interviews, and documentation studies. The research respondents numbered 18 people selected using a purposive sampling technique, consisting of the chairperson, secretary, and treasurer of Gapoktan. System testing was conducted using Black Box Testing to test system functionality, while user evaluation was conducted through questionnaires to measure ease of use, system effectiveness, work efficiency, and user satisfaction. The results showed that all system functions ran as needed with a test success rate of 100%. The user evaluation results obtained an average score of 90.00%, categorized as very good, consisting of aspects of ease of use of 91.11%, system effectiveness of 88.89%, work efficiency of 86.67%, and user satisfaction of 93.33%. These results indicate that the developed system is able to improve the quality of data management, accelerate the administrative process, and support more effective report preparation within the Gapoktan environment.